Working-Class Lesbian Life - Taylor, Yvette. author. aut Link
IX, 220 p.
Keywords: This is an original study of women self-identified as working-class and lesbian, showing the significance of class and sexuality in their biographies, everyday lives and identities. It provides insight, a critique of queer theory and an empirical interrogation of the embodied, spatial and material intersection of class and sexuality.